2021
DOI: 10.1073/pnas.2010523118
|View full text |Cite
|
Sign up to set email alerts
|

Cargo competition for a dimerization interface restricts and stabilizes a bacterial protease adaptor

Abstract: Bacterial protein degradation is a regulated process aided by protease adaptors that alter specificity of energy-dependent proteases. In Caulobacter crescentus, cell cycle–dependent protein degradation depends on a hierarchy of adaptors, such as the dimeric RcdA adaptor, which binds multiple cargo and delivers substrates to the ClpXP protease. RcdA itself is degraded in the absence of cargo, and how RcdA recognizes its targets is unknown. Here, we show that RcdA dimerization and cargo binding compete for a com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Our results suggest the midnolin-proteasome pathway may represent a general mechanism by which the proteasome bypasses the traditional ubiquitination system to achieve selective degradation of many nuclear proteins. It has been reported that in bacteria, which do not contain the ubiquitin-proteasome system, a hierarchy of adaptors mediate selective degradation of diverse proteins by the proteasome-equivalent ClpXP protease complex ( 54 , 55 ). Thus, it will be of interest to determine whether, in the course of evolution, additional proteins have evolved to recruit proteins directly to the proteosome for degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest the midnolin-proteasome pathway may represent a general mechanism by which the proteasome bypasses the traditional ubiquitination system to achieve selective degradation of many nuclear proteins. It has been reported that in bacteria, which do not contain the ubiquitin-proteasome system, a hierarchy of adaptors mediate selective degradation of diverse proteins by the proteasome-equivalent ClpXP protease complex ( 54 , 55 ). Thus, it will be of interest to determine whether, in the course of evolution, additional proteins have evolved to recruit proteins directly to the proteosome for degradation.…”
Section: Discussionmentioning
confidence: 99%
“…It took several laboratories and many publications to begin to establish these regulatory functions. It is also important to note that several of these adaptors are themselves substrate for degradation by the Clp system ( 71 ). Because elucidation of Clp adaptor functions and even substrates can be so daunting, we carried out a comprehensive analysis of these 22 candidate adaptors and substrates through computational analysis (summarized in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…RcdA dimers can readily be detected in solution, and critically RcdA and cargo both compete for the same RcdA interface. This competition determines the fate of RcdA itself since RcdA homodimers are degraded by ClpXP, while bound cargo stabilizes RcdA against proteolysis 52,53 .…”
Section: Discussionmentioning
confidence: 99%